METHODOLOGY OF ECONOMICS AND FORMALIZATION ISSUE IN SCIENCE - A. O. Ovcharov (Russian Journal of Economics and Law, 2013)
The article views the methodology issues of the modern science of Economics. The content and types of economic methodology are displayed; the system of scientific methods in economics is presented. The content of two methods (analysis and hypothetical-deductive method) is specified referring to economic research. Various viewpoints on the topical issue of economics formalization are indicated.